Empowering Household Finances: Housewives’ Financial Literacy, Confidence, Risk Appetite, and Dependence in Indonesia - Dewanti, Putriyuki; Viverita, Viverita (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study analyzes the influence of financial literacy, investment confidence, risk appetite, and dependence status on the financial decision-making of housewives in Indonesia. The academic contribution lies in integrating psychological and sociocultural factors into the financial literacy–behavior nexus, offering a nuanced perspective on household financial agency. A survey of 230 housewives was analyzed using structural equation modeling (SmartPLS) to test the proposed relationships. Results show that financial literacy interacts with investment confidence, risk appetite, and dependence status, yet its impact is contingent on the ability to apply knowledge in everyday contexts. Investment confidence enhances proactive financial behavior, while risk appetite encourages more diverse decisions. Conversely, high dependence on others restricts autonomy in financial choices. The findings emphasize the need for tailored financial education programs that strengthen housewives’ independence and improve overall household financial well-being.